Moslem Consumer Behavior on Buying Ticket Decision at Halal Tourism Fruit Garden Mekarsari Cileungsi - Muhammad Salman Alfarisi; Rofiq Noorman Haryadi; Denok Sunarsi (Sharia Business Management Department of STEBIS Bina Mandiri, 2022)
This study aims to determine how much influence Muslim consumer behavior has on the decision to buy admission tickets at halal tourism fruit garden Mekarsari Cileungsi Bogor. The subvariables studied from consumer behavior are recognizing needs, seeking information, evaluating alternatives. While purchasing decisions, namely, product selection, brand selection, purchase time. This study is an associative quantitative study, with a significance level of 0.1 (10%) and a confidence level of 90%. While the sample used was 64 visitors from the calculation of Slovin's theory. Methods of data collection using primary data system, namely observation and questionnaires, secondary data, namely literature study. Testing the instrument using validity and reliability tests, for data analysis methods using frequency distribution analysis, simple linear regression, correlation coefficient, coefficient of determination, and t test. Data calculation is done manually and using statistical software. The results showed that the influence of Muslim consumer behavior on the decision to buy admission tickets at at halal tourism fruit garden Mekarsari Cileungsi Bogor. Analysis of the frequency data was very good at 3.91 and the saving decision was very good at 3.95. In linear regression analysis Y = 24,222 + 0,802X the correlation coefficient is felt to be strong at 0.796, the coefficient of determination is 63.4% in the t test, it is obtained t arithmetic > t table 10.35 > 1.670. So Ho is rejected, Ha is accepted, meaning that there is a significant influence between the behavior of Muslim consumers on the decision to buy admission tickets at halal tourism fruit garden Mekarsari Cileungsi Bogor